Male facial attractiveness and masculinity may provide sex‐ and culture‐independent cues to semen quality. (24th July 2014) - Soler, C.; Kekäläinen, J.; Núñez, M.; Sancho, M.; Álvarez, J. G.; Núñez, J.; Yaber, I.; Gutiérrez, R.
Abstract Phenotype‐linked fertility hypothesis (PLFH) predicts that male secondary sexual traits reveal honest information about male fertilization ability. However, PLFH has rarely been studied in humans. The aim of the present study was to test PLFH in humans and to investigate whether potential ability to select fertile partners is independent of sex or cultural background. We found that on the contrary to the hypothesis, facial masculinity was negatively associated with semen quality. As increased levels of testosterone have been demonstrated to impair sperm production, this finding may indicate a trade‐off between investments in secondary sexual signalling (i.e. facial masculinity) and fertility or status‐dependent differences in investments in semen quality. In both sexes and nationalities (Spanish and Colombian), ranked male facial attractiveness predicted male semen quality. However, Spanish males and females estimated facial images generally more attractive (gave higher ranks) than Colombian raters, and in both nationalities, males gave higher ranks than females. This suggests that male facial cues may provide culture‐ and sex‐independent information about male fertility. However, our results also indicate that humans may be more sensitive to facial attractiveness cues within their own populations and also that males may generally overestimate the attractiveness of other men to females.